Is abdominal hollowing exercise using real-time ultrasound imaging feedback helpful for selective strengthening of the transversus abdominis muscle?: A prospective, randomized, parallel-group, comparative study. Issue 27 (July 2018) - Lee, Dae Hee; Hong, Seong Kyung; Lee, Yang-Soo; Kim, Chul-Hyun; Hwang, Jong Moon; Lee, Zeeihn; Kim, Jong Min; Park, Donghwi
Abstract : Abstract: Despite the importance of strengthening of the transversus abdominis (TrA) muscle in individuals with low back pain, the effect of real-time ultrasound imaging on maintenance in selective strengthening of abdominal hallowing exercise (AHE) performance has not been investigated. So, the aim of this study was to investigate the effects of AHE with real-time ultrasound imaging feedback on selective reinforcing the TrA muscle. Twenty healthy subjects were enrolled prospectively and randomized to train AHE for 2 weeks either by conventional feedback (group A) or by visual feedback from real-time ultrasound imaging additional to conventional feedback (group B). The changes in thickness of TrA, internal oblique abdominal muscle (IO), and external oblique abdominal muscle (EO) were measured using the ultrasonography. The changes in muscle activities of TrA-IO and EO were measured using surface electromyography. The thickness of TrA, IO, and EO muscles in resting was not significantly changed in both groups A and B. However, the ratio of root mean square (RMS) values of TrA-IO/EO muscles, which mirrors selective contraction of TRA-IO muscles against EO muscle, was significantly higher in group B than in group A. In healthy subjects, training with AHE using real-time ultrasound imaging feedback may be a useful additional method to conventional feedback for strengthening the TrA muscles selectively.